Determination of Atenolol and Hydrochlorothiazide in Pharmaceutical Preparation Using RP-HPLC - Antakli, Saad; Nejem, Leon; Joumaa, Moustafa Alabo (Journal of natural sciences, life and applied sciences, 2022)
A (Reversed Phase High Performance Liquid Chromatography) (RP-HPLC) method was Development for the determination of Atenolol (ATE) and Hydrochlorothiazide (HCT) in tablets formulations. Isocratic Elution Chromatography analysis was achieved with (methanol: phosphoric acid) (pH = 4) in ratio of 70:30 (v/v) as mobile phase, the analytical is done by C18 column and UV detector at 220 nm, pump flow rate was 1.2 mL/min and sample injection volume 20 μL. The proposed method was successfully applied to analysis individual or mixture of (ATE) and (HCT) in Syrian trademark drugs. All studied samples showed that the drug levels were conformed to British Pharmacopeia. Finally, the method is simple, selective and suitable for routine quality control analysis.